Play-Based Learning with Cantol Method for Developing Early Children's Linguistic Intelligence - Zulfa Isnia Azmi; Azizah Nurul Fadlilah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
This study describes the implementation of playing while learning children with the hook method and its implications for language development for early childhood at Roudhoh Depok tutoring. This research is descriptive research with a qualitative approach. The subjects of this study were PAUD students and educators at the Roudhoh Learning Guidance, Depok. Methods of data collection with interviews and documentation. Data analysis uses data analysis techniques from the Miles and Huberman model, consisting of data reduction, data presentation, and concluding. The results showed that the implementation of playing while learning with the hook method is a learning method that is given to introduce letters and how to read without coercion but with games that use visual aids and systems. Not spell, but hooks, which combine two letters (consonants and vowels) read together. The implication for the development of linguistic intelligence in early childhood is that it can produce students who can develop linguistic intelligence according to standards.